2016
DOI: 10.1007/s11136-016-1472-6
|View full text |Cite
|
Sign up to set email alerts
|

In 6- to 8-year-old children, cardiorespiratory fitness moderates the relationship between severity of life events and health-related quality of life

Abstract: Recent stressful experiences alone were not sufficient to explain negative health outcomes in young children. Children with low cardiorespiratory fitness levels experienced lower psychological wellbeing when they were exposed to critical life events. More research is needed to find out whether similar findings emerge with objective physical activity measurements and when critical life events are assessed over longer periods of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 70 publications
1
21
1
Order By: Relevance
“…Physical inactivity, low physical fitness, and perceived stress during childhood and adolescence are presumed to be risk factors for various chronic conditions including cardiovascular diseases (Petersen et al, 2012 ; Bergh et al, 2015 ), depressive symptoms (Motl et al, 2004 ; Brunet et al, 2013 ), pain and subjective health complaints (Sundblad et al, 2008 ). In turn, physical fitness and physical activity are presumed to moderate the negative effects of stress and protect against stress-related health complaints in children and adolescents (Haugland et al, 2003 ; Hegberg and Tone, 2015 ; Gerber et al, 2017a ). Gerber et al ( 2017a ) recently revealed that children (6- to 8-year-old) with higher physical fitness levels, in terms of cardiorespiratory fitness (measured by 20 m shuttle run test), experienced higher levels of psychological well-being relative to their less fit peers when exposed to elevated stress levels (parental questionnaire), and higher levels of physical wellbeing when stress levels were low.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Physical inactivity, low physical fitness, and perceived stress during childhood and adolescence are presumed to be risk factors for various chronic conditions including cardiovascular diseases (Petersen et al, 2012 ; Bergh et al, 2015 ), depressive symptoms (Motl et al, 2004 ; Brunet et al, 2013 ), pain and subjective health complaints (Sundblad et al, 2008 ). In turn, physical fitness and physical activity are presumed to moderate the negative effects of stress and protect against stress-related health complaints in children and adolescents (Haugland et al, 2003 ; Hegberg and Tone, 2015 ; Gerber et al, 2017a ). Gerber et al ( 2017a ) recently revealed that children (6- to 8-year-old) with higher physical fitness levels, in terms of cardiorespiratory fitness (measured by 20 m shuttle run test), experienced higher levels of psychological well-being relative to their less fit peers when exposed to elevated stress levels (parental questionnaire), and higher levels of physical wellbeing when stress levels were low.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, physical fitness and physical activity are presumed to moderate the negative effects of stress and protect against stress-related health complaints in children and adolescents (Haugland et al, 2003 ; Hegberg and Tone, 2015 ; Gerber et al, 2017a ). Gerber et al ( 2017a ) recently revealed that children (6- to 8-year-old) with higher physical fitness levels, in terms of cardiorespiratory fitness (measured by 20 m shuttle run test), experienced higher levels of psychological well-being relative to their less fit peers when exposed to elevated stress levels (parental questionnaire), and higher levels of physical wellbeing when stress levels were low. Furthermore, children with higher physical activity, as reported by their parents, demonstrated better overall health-related quality of life (parental questionnaire), but only if they experienced low stress (Gerber et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations